KERAGAMAN FENOTIPE DAUN MERANTI PUTIH (Anthoshorea montigena) DI PULAU SERAM - Christofer Wattimena; Johan M. Matinahoru; Irwanto Irwanto (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study examines the phenotypic diversity of White Meranti (Anthoshorea montigena) leaves in Seram Island by analyzing leaf morphology across four sites: Honitetu, Latu, Haya, and Masihulan. The research aims to identify similarities in leaf characteristics among locations and to evaluate the influence of environmental factors on phenotypic variation. A purposive sampling survey was conducted, with both quantitative and qualitative data analyzed using ANOVA and regression. Results revealed significant variation in leaf area, primary vein length, and number of secondary veins. Environmental factors contributed differently at each site: light intensity affected 32.54% of leaf area in Honitetu, air humidity 30.86% in Latu, soil fertility 51.98% in Haya, and humidity 22.41% in Masihulan. The phenogram indicated 85% similarity between Honitetu and Latu, 80% with Haya, and greater divergence with Masihulan. These findings provide valuable insights for future breeding and conservation of White Meranti (Anthoshorea montigena).